2019
DOI: 10.1097/bpo.0000000000001010
|View full text |Cite
|
Sign up to set email alerts
|

Motion Necessary to Achieve Mallet Internal Rotation Positions in Children With Brachial Plexus Birth Palsy

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…In recent years, different surgical techniques including internal rotation osteotomy have been introduced to prevent loss of shoulder internal rotation (Abdel-Ghani et al., 2012; Sibinski et al., 2012). Although Russo et al. (2019) recommended evaluating shoulder internal rotation with hand to belly movement only prior to the surgery, the results of our study revealed that, due to the presence of postural internal rotation, shoulder internal rotation should be evaluated not only actively but also passively.…”
Section: Discussionmentioning
confidence: 77%
“…In recent years, different surgical techniques including internal rotation osteotomy have been introduced to prevent loss of shoulder internal rotation (Abdel-Ghani et al., 2012; Sibinski et al., 2012). Although Russo et al. (2019) recommended evaluating shoulder internal rotation with hand to belly movement only prior to the surgery, the results of our study revealed that, due to the presence of postural internal rotation, shoulder internal rotation should be evaluated not only actively but also passively.…”
Section: Discussionmentioning
confidence: 77%
“…Visual grading based on the Active Movement Scale [ 10 ] and modified Mallet score [ 11 ] was developed to facilitate long-term follow-ups for range of motion and muscle function in BPBI patients and is used extensively throughout the world [ 5 ]. The scales are efficient and easy to implement in clinic but have been criticized as too subjective and missing crucial functional deficiencies [ 12 , 13 , 14 , 15 , 16 ]. Further, these scales do not describe how the glenohumeral joint and scapulothoracic articulation contribute to global shoulder (i.e., thoracohumeral) shoulder motion.…”
Section: Introductionmentioning
confidence: 99%
“…Goniometry and Medical Research Council 0–5 grading [ 20 ] are alternative methods to assess changes in range of motion and muscle strength but are difficult to implement in infants and younger children. Another approach is to use a three-dimensional kinematic analysis of the shoulder complex [ 12 , 21 , 22 , 23 ]. Such methods have been used to identify deficient external rotation in the glenohumeral joint and the global movement of the shoulder in children with BPBI when performing tasks of the modified Mallet scale [ 12 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is often challenging to achieve very wide arcs of shoulder rotation and elevation, but not many activities require two hands behind the back, far out to the sides or overhead. A roughly 90° arc of shoulder rotation that allows placement of the hand on the belly (at the extreme of internal rotation) 1 to just beyond neutral position (forearm forward at the extreme of external rotation) is arguably the most functionally useful range of movement in that axis. Achieving that range of active rotation allows for midline (dressing, buttoning, perineal care), bimanual and desktop function.…”
Section: Introductionmentioning
confidence: 99%